1932
DOI: 10.1021/ja01345a019
|View full text |Cite
|
Sign up to set email alerts
|

GERMANIUM. XXXIX. THE POLYMORPHISM OF GERMANIUM DIOXIDE1

Abstract: This article is based upon the thesis presented to the Faculty of the Graduate School of Cornell University by D. S. Morton in partial fulfilment of the requirements for the degree of Doctor of Philosophy.2 Goldschmidt, Naturwissenschaften, 14, 295 (1926).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

1934
1934
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 0 publications
6
73
0
Order By: Relevance
“…This difference is due to the markedly different Ge-O bond length and bond energy for t he two forms. For tetragonal Ge0 2, the Ge-O bond length [3] is 1.86 A. The bond length for the h exagonal Ge02 has not been given, but it is likely that i t is shorter than 1.86 A, corresponding to a stronger bond and larger bondstretching force constant and vibrational frequency.…”
Section: 5 Ge02mentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is due to the markedly different Ge-O bond length and bond energy for t he two forms. For tetragonal Ge0 2, the Ge-O bond length [3] is 1.86 A. The bond length for the h exagonal Ge02 has not been given, but it is likely that i t is shorter than 1.86 A, corresponding to a stronger bond and larger bondstretching force constant and vibrational frequency.…”
Section: 5 Ge02mentioning
confidence: 99%
“…Because coordination of silicon in coe ite [2] has not been established, one of the objectives of this work was to furnish evidence for either the fourfold coordination of the other polymorphs of Si02 or for a different coordination. I n the tetragonal form of Ge02 the germanium atom has a sixfold coordination with oxygen, whereas in the quartz-type hexagonal Ge0 2 the germanium atom has the fourfold coordination of silicon in quartz [3,4]. A similar tetragonal form of silica is not known but has been predicted by analogy with germania.…”
Section: Introductionmentioning
confidence: 99%
“…One modification is of the a-quartz type (Zaehariasen, 1928) and thus has 4:2 coordination; the other form, of the futile type (Laubengayer & Morton, 1932), accordingly has 6:3 coordination. These latter investigators have shown quartz-like GeOe to be actually the stable high-temperature phase.…”
Section: Introductionmentioning
confidence: 99%
“…GeO 2 crystallizes with the bulk rutile structure (space group P4 2 /mnm) [2,19,20]. In Figure 1 a schematic representation of the lattice is depicted.…”
Section: Methodsmentioning
confidence: 99%
“…GeO 2 occurs in three stable forms at ambient temperature [1]. The first form has the rutile tetragonal structure (P4 2 /mnm) with octahedral coordination [2]. The second form has the trigonal structure of α-quartz [3], with tetrahedral coordination.…”
Section: Introductionmentioning
confidence: 99%